#TITLE_ALTERNATIVE# - Anggraeni (NIM 250 03 082), Dewi
Abstract: Transportation system, especially in public transportation will run well if the needs of user and operator efficiently and effectively complete, which is depends on the operational management of the public transportation itself. The aim of research is to evaluate operators service performance (operational), with indicator users is Waiting Time and Load Factor. One method to achieve the aim of this study is by applying policy variable which can be hint in operational of public transportation. Research object is limited only in two routes, namely Yotefa Terminal - Kotaraja and Yotefa Terminal - Uncen Baru routes. The secondary data has been collecting including road network map, route, number of armada and fare. Mearnwhile the primary data received from interview survey to get user characteristic data, drivers interview to get vehicle operational data , and also on board survey during operation time to get passenger amount of public transportation and vehicle operational data (Cycle Time), static survey at terminal to get the headway. Policy variable in this research is number of vehicle. The method used in this research is sensitivity analysis in seeing influence policy variable to indicator users and operators, and examined method of each indicator level to pick the best scenario. Analysis result shows that the service performance of public transportation if looked from the effective point of view to user exhibits the high simplicity level and travel time to reach waiting place can be achieve on foot. Indicator performance of each stakeholder was not completely appropriate with the standard. Indicator performance from to user that the average waiting time is 0,88 minute, while waiting time standard is 5 - 10 minute; load factor along the line is 0,42 (41,5degree), where standard value is 0,7. Indicator performance from operator side is the profit, the profit for line Yotefa Terminal - Uncen Baru values is positive, while for line Yotefa Terminal - Kotaraja in work day values is negative. This is because the fare unit is lower than Minimum Recovery Cost (BPM) value. Policy variable number of vehicle which having a high sensitivity level to indicators. The best operational policy with assuming that the same interest level of user and operator is by reducing vehicle until 20degree from existing condition. Meanwhile, if assumed that the interest level of user bigger than operator is by adding vehicle until 20degree. And if assumes that the interest level of user smaller than operator is by reducing vehicle until 20degree.